Ransomware and reputation - Anna Cartwright; Edward Cartwright (Games, 2019)
Ransomware is a particular form of cyber-attack in which a victim loses access to either his electronic device or files unless he pays a ransom to criminals. A criminal's ability to make money from ransomware critically depends on victims believing that the criminal will honour ransom payments. In this paper we explore the extent to which a criminal can build trust through reputation. We demonstrate that there are situations in which it is optimal for the criminal to always return the files and situations in which it is not. We argue that the ability to build reputation will depend on how victims distinguish between different ransomware strands. If ransomware is to survive as a long term revenue source for criminals then they need to find ways of building a good reputation.
Keywords: 330; ransomware; repeated game; reputation; trust